2011
DOI: 10.1128/jvi.01703-10
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus LMP1 Activates EGFR, STAT3, and ERK through Effects on PKCδ

Abstract: Epstein-Barr virus (EBV) is a ubiquitous herpesvirus that infects more than 90% of the world's adult population and is linked to multiple malignancies, including Burkitt lymphoma, Hodgkin disease, and nasopharyngeal carcinoma (NPC). The EBV oncoprotein LMP1 induces transcription of the epidermal growth factor receptor (EGFR), which is expressed at high levels in NPC. EGFR transcription is induced by LMP1 through a p50 NFB1-Bcl-3 complex, and Bcl-3 is induced by LMP1-mediated activation of STAT3. This study rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
118
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 49 publications
13
118
1
Order By: Relevance
“…Constitutive expression of pSTAT3 and survivin is a wellknown characteristic of tumor cells and cells transformed by oncogenic viruses, including KSHV and EBV (14,(26)(27)(28). Our study of VZV shows that STAT3 activation and survivin expression also support lytic herpesvirus replication not only in vitro but also in differentiated human skin cells within their tissue microenvironment in vivo.…”
Section: Discussionmentioning
confidence: 80%
“…Constitutive expression of pSTAT3 and survivin is a wellknown characteristic of tumor cells and cells transformed by oncogenic viruses, including KSHV and EBV (14,(26)(27)(28). Our study of VZV shows that STAT3 activation and survivin expression also support lytic herpesvirus replication not only in vitro but also in differentiated human skin cells within their tissue microenvironment in vivo.…”
Section: Discussionmentioning
confidence: 80%
“…Notably, overexpression of ICAM1 is generally seen in various types of EBV-related cancers such as NPC, GC and NHL [27][28][29]. Similarly, exosomal LMP1 also induced epidermal growth factor receptor (EGFR) expression [30] which is another important receptor that modulates a cascade of oncogenic signalling pathways such as mitogen-activated protein kinase (MAPK), c-Jun N terminal kinase (JNK), phosphatidylinositol 3 kinase (PI3K) and nuclear factor kappa-beta (NF-κB) in EBV cancers [31,32]. In line with of the role of exosomal LMP1 in EGFR-related pathways, Meckes and co-workers also demonstrated that exosomal LMP1…”
Section: Novel Implications Of Exosomes In Diagnosis and Treatment Ofmentioning
confidence: 99%
“…As summarized in Table 1, cumulative findings suggest that exosomal LMP1 promotes the growth and progression of EBV-associated cancers. While the cell-associated or intracellular LMP1 plays multiple roles in EBV latent infection and cancer pathogenesis particularly by modulating NF-κB, PI3K/AKT, MAPK and JAK/STAT pathways [31,32], future investigations are warranted to demonstrate whether the exosomal LMP1 similarly carries these tumorigenic functions and pathogenic effects in EBV-associated cancers.…”
Section: Novel Implications Of Exosomes In Diagnosis and Treatment Ofmentioning
confidence: 99%
“…EBV-encoded latent membrane proteins, LMP1, LMP2A, and 2B: LMP1 acts as a constitutively active receptor in a ligand-independent manner, mimicking CD40 (Gires et al, 1997). It activates the majority of signaling pathways that are known to be activated in HRS cells, including NF-κB, PI3K/ Akt/mTOR, and Jak/STAT pathways, thereby induces various antiapoptotic proteins and cytokines (Chen et al, 2003;Lambert and Martinez, 2007;Kung et al, 2011). Since normal germinal center B cells that lack BCR in their cell surfaces are eliminated by apoptosis, the HRS precursor cell is assumed to be rescued by LMP1 that plays a critical role in the protection of B cells from apoptotic death by up-regulating several antiapoptosis genes (Asso-Bonnet et al, 1998;Lee et al, 2003).…”
Section: Ebna1mentioning
confidence: 99%